Analysis of the coverage of the Chilean digital press during the legislative discussion of the Gender Identity Act in 2018 - Ibarra Yáñez, Pía; Amoyao Bravo, Camila; Román Álvarez, Eduardo (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
This article discusses digital media coverage of the discussion of the Gender Identity Act in Chile in September 2018. The study was approached for three days before the vote, on the day of the congressional debate and three days after it was approved. It was raised to know how the digital media builds reality, being the main objective to analyze the coverage of digital press during that episode, arguing as hypothesis that the press made an unquesqueous coverage, mainly by the management of sources. Data obtained through the NewsReport platform were analyzed, yielding media distribution with the highest news coverage, the most relevant political actors, keywords and news sources, and the time frame of mediatization. Concluding that the press tended to neutrality, but with a precarious source management.
Keywords: Gender Identity Act; Chile; Construction of reality; Press; Gender